Detailed functional characterization of glycosylated and nonglycosylated variants of malaria vaccine candidate PfAMA1 produced in Nicotiana benthamiana and analysis of growth inhibitory responses in rabbits. Issue 2 (18th September 2014) - Boes, Alexander; Spiegel, Holger; Edgue, Gueven; Kapelski, Stephanie; Scheuermayer, Matthias; Fendel, Rolf; Remarque, Edmond; Altmann, Friedrich; Maresch, Daniel; Reimann, Andreas; Pradel, Gabriele; Schillberg, Stefan; et al.
Summary One of the most promising malaria vaccine candidate antigens is the Plasmodium falciparum apical membrane antigen 1 (PfAMA1). Several studies have shown that this blood‐stage antigen can induce strong parasite growth inhibitory antibody responses. PfAMA1 contains up to six recognition sites for N‐linked glycosylation, a post‐translational modification that is absent in P. falciparum. To prevent any potential negative impact of N‐glycosylation, the recognition sites have been knocked out in most PfAMA1 variants expressed in eukaryotic hosts. However, N‐linked glycosylation may increase efficacy by improving immunogenicity and/or focusing the response towards relevant epitopes by glycan masking. We describe the production of glycosylated and nonglycosylated PfAMA1 in Nicotiana benthamiana and its detailed characterization in terms of yield, integrity and protective efficacy. Both PfAMA1 variants accumulated to high levels (>510 μg/g fresh leaf weight) after transient expression, and high‐mannose‐type N‐glycans were confirmed for the glycosylated variant. No significant differences between the N. benthamiana and Pichia pastoris PfAMA1 variants were detected in conformation‐sensitive ligand‐binding studies. Specific titres of >2 × 106 were induced in rabbits, and strong reactivity with P. falciparum schizonts was observed in immunofluorescence assays, as well as up to 100% parasite growth inhibition for both variants, with IC50 values of 35 μg/mL. Competition assays indicated that a number of epitopes were shielded from immune recognition by N‐glycans, warranting further studies to determine how glycosylation can be used for the directed targeting of immune responses. These results highlight the potential of plant transient expression systems as a production platform for vaccine candidates.